Treatment options for unilateral vestibular schwannoma: a network meta-analysis - Xianhao Huo; Xu Zhao; Xiaozhuo Liu; Yifan Zhang; Jihui Tian; Mei Li (BMC Cancer)
Abstract This study aimed to explore the effect of observation, microsurgery, and radiotherapy for patients with vestibular schwannoma (VS). We searched PubMed, Medline, Embase, Web of Science, and Cochrane library from their establishment to July 31, 2024. 34 non-RCTs and 1 RCT that included 6 interventions were analyzed. We found the MS, and different SRS all had better tumor local control rates. Regarding preserved hearing, the order from the highest to the lowest was FSRT 5 fractions, FSRT 3 fractions, SRS, ConFSRT, Observation, and MS. Regarding improvement in the rate of tinnitus, the order from the highest to the lowest was ConFSRT, FSRT 3 fractions, SRS, Observation, MS, and FSRT 5 fractions. In terms of improving the rate of disequilibrium/vertigo, the order from the highest to the lowest was SRS, Observation, FSRT 3 fractions, FSRT 5 fractions, MS, and ConFSRT. In terms of protection of the trigeminal nerve, the order from the highest to lowest was observation, SRS, ConFSRT, FSRT 3 fractions, FSRT 5 fractions, and MS. Lastly, in terms of protection of the facial nerve, the order from the highest to lowest was SRS, ConFSRT, Observation, FSRT 3 fractions, FSRT 5 fractions, and MS. In patients with VS, MS and radiosurgery showed better local tumor control rates; however, compared with MS, different SRS all provided better protection of nerve function and improved the symptoms of vestibular function and tinnitus, among which the best was SRS. Therefore, in these patients, SRS may be a promising alternative treatment.